MODEL KOMUNIKASI GENERASI MUDA: STUDI KASUS KRITIK AURA CINTA TERHADAP DEDDY MULYADI - Nadiya Fuada; Husein Haidar Ali; Rohmadatul Huda; Diya Ayu Luspita Wulansuci (Jurnal Intelek Insan Cendikia, 2025)
This study examines the communication model of the younger generation in conveying social criticism through digital media, using the case study of Aura Cinta’s criticism against Deddy Mulyadi. The research focuses on analyzing political communication models, hyperpersonal communication based on CMC, and mass communication in the context of delivering social criticism. The research method used is a descriptive qualitative approach with discourse analysis on the criticism video uploaded by Aura Cinta on social media. The results indicate that the younger generation effectively utilizes digital media to express their critical views with a clear, assertive, and participatory communication style. Through digital platforms, the social criticism conveyed has a high spreadability and significantly influences public opinion. These findings suggest that social media is an important instrument in amplifying the voices of the younger generation in public discourse.